Sosialisasi sistem bagi hasil antara pemilik modal dan penggarap lahan pertanian pada Kelompok Tani Ciole-Ole di Desa Alamendah - Kurniasih, Nia; Safariah, Iin; Nurhasanah, Erna (Penamas: Journal of Community Service, 2025)
The socialization program aims to provide an understanding of the importance of implementing a profit-sharing system based on Sharia principles between capital owners and agricultural land cultivators. The program was implemented in the Ciole-Ole farmer group, Alamendah Village, Rancabali Subdistrict, Bandung Regency. Based on an initial survey, it was found that the working relationship between capital owners and land cultivators had not adopted a proper profit-sharing system, often leading to unfair distribution of profits, especially when harvest yields were unsatisfactory. The activity was conducted through face-to-face socialization using presentation techniques and interactive discussions. To measure the effectiveness of the activities, an evaluation was conducted through pre-tests and post-tests using a questionnaire instrument. The results of the activities showed an increase in community knowledge, particularly in understanding and applying a fair profit-sharing system by Sharia principles. Pre-test data indicated that most group members did not understand adequately, while post-test results demonstrated a significant improvement after the socialization activities were conducted.